A Comparison of A 4% Modified Fluid Gelatin and A 6% Hydroxyethyl Starch on Haemodilution, Colloid Osmotic Pressure, Haemostasis and Renal Parameters in Healthy Ponies. (September 2015) - Gratwick, Z.; Viljoen, A.; Page, P.C.; Goddard, A.; Fosgate, G.T.; Lyle, C.H.
Abstract : Reasons for performing study: Adverse effects on renal health and haemostasis have been documented in human patients administered hydroxyethyl starches (HES). Gelatins could provide useful substitutes for HES should similar adverse effects be identified in horses. Objectives: To compare the effects of a 4% modified fluid gelatin (MFG) with a 130/0.4 6% tetrastarch (TES) on haemodilution, colloid osmotic pressure (COP), haemostasis and renal parameters in healthy ponies. Study design: Randomised crossover. Methods: Three treatments (A = 10 ml/kg bwt TES, B = 10 ml/kg bwt MFG and C = 20 ml/kg bwt MFG) were administered to 6 healthy ponies with a one‐week washout period. Packed cell volume (PCV), total serum protein (TSP), COP, platelet count, fibrinogen, prothrombin time (PT), activated partial thromboplastin time (aPTT) and thromboelastography (TEG) were measured at baseline and at multiple time points up to 24 h post infusion. Serum creatinine, urine specific gravity (USG), urine protein:creatinine (UPC), urine GGT:creatinine (UGC) and urine sediment examination (USE) were performed before and 24 h after each treatment, and one week after the final treatment. Results: All treatments caused significant haemodilution and increases in COP with treatment C having a significantly greater effect on PCV than other treatments. The platelet count decreased with all treatments and was significantly lower for treatment C compared with treatment B. No significant differences were observed in any TEG parameter within or between treatments. No significant differences in PT, aPTT or fibrinogen were observed between treatments. Serum creatinine, UGC and UPC did not change significantly pre‐ and post study. USG and USE remained within normal limits. Conclusions: 4% MFG could be considered as an alternative to 130/0.4 6% TES for volume expansion and oncotic support. Neither MFG nor TES were associated with clinically significant adverse effects on haemostasis or renal parameters. Ethical animal research:  This research was approved by the University of Pretoria's Animal Ethics Committee. The animals used in the study were part of a research herd belonging to The University of Pretoria.Sources of funding:  The Department of Companion Animal Clinical Studies, Faculty of Veterinary Science, University of Pretoria, The Abe Bailey Trust Fund, The South African Veterinary Foundation and The South African Equine Veterinary Association.Competing interests:  None declared.